Sexual Harassment Against Women on Social Media - Rakatiwi, Yolanda; Halwati, Umi; Nawawi (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
In the current era of globalization, information and communication technology is developing rapidly, one of which is in the field of social media. But along with the rapid development of technology, there are parties who abuse the functions of Facebook social media. The current problem on Facebook is sexual harassment, where there are two parties communicating online and these two parties are the perpetrator and the victim. The perpetrator sent a short message on Facebook that was initially complimentary but became sexually suggestive. The aim of this research is to find out the underlying causes of sexual harassment and reduce the number of sexual harassment on Facebook. The method in this research uses a case study which is studied qualitatively by distributing an online questionnaire in the form of a Google form, then conducting interviews with several sources, namely two victims of sexual harassment. Data collection techniques used observations from newspapers and respondents from distributed online questionnaires and conducting structured interviews. The results of this research show that sexual harassment that occurs on social media is divided into written harassment, verbal harassment, visual harassment and real harassment. The response from female social media users was that most of them regretted the sexual harassment activities that occurred. Acts of sexual harassment also have negative impacts on victims, such as post-traumatic stress disorder (PTSD) and psychological impacts that trigger a series of complications, especially regarding the physical health of victims of sexual harassment on social media.